Integrating Siri’ na Pacce on Pancasila and Civic Education Subject in Elementary Schools - Azis, Abdul; Komalasari, Kokom; Sapriya, Sapriya; Rahmat, Rahmat (International Conference on Elementary Education, 2021)
As part of the nation’s cultural wealth, local culture needs to be bequeathed to the younger generation through integration in school learning activities. Siri’ na pacce is a philosophy of the Bugis- Makassar tribe, one of Indonesia’s major tribes. Siri’ na pacce is local wisdom that contains noble values, like sipakatau, reso, and pacce. The manifestation of sipakatau is respect for others. The embodiment of reso is the seriousness of doing something to achieve Allah’s grace, God of the universe. Meanwhile, the expression of pacce is caring for each other and the environment. The noble values can be integrated into elementary school learning through exemplary, consistently habituation, or insert the explanation of the values to the subject matter.